Ruling from the grave? : the political instrumentalization of Robert Mugabe’s corpse in contemporary Zimbabwean politics - Mpofu, Shepherd (SAGE, 2022)
This qualitative research is a critical analysis of news media reports, political debates, and political and family behaviours to interrogate the centrality of death, corpses, funeral and mortuary rituals in African politics by using the death of Zimbabwe’s former President, Robert Mugabe as a case study. At death, it became clear what a polarizing and yet unifying figure Mugabe was. His dead body became a contested political asset. The paper explores how Mugabe’s family resisted President Mnangagwa’s attempts at gaining control of Mugabe’s dead body for political expediency after he disposed of him in a military coup in 2017. The paper concludes that, true to Mugabe’s wife’s assertions that he will rule Zimbabwe from the grave, Mugabe, as a dead man, caused some considerable political tensions between his family and ruling magnifying the coup architects’ legitimacy challenges and his power in Zimbabwean politics.
Journal article published in the Journal of Asian and African studies · September 2022
Keywords: Corpse-power; Mugabe; Zimbabwe; Corpse; Heroes’ Acre; Mnangagwa; Zimbabwe -- Politics and government; Mugabe, Robert Gabriel, -- 1924-2019